Kajian Ekranisasi Novel Dan Film Merindu Cahaya De Amstel - Rahmi Suryati; Dian Hartati (Peneliti.net, 2023)
The film that is included in the big screen is an adaptation of a novel. However, not everything in the novel will be found in the film. Because a film is relatively shorter, there are several changes in the adaptation process. The aim of this research is to find out the differences and to describe the forms of changes in the ecranization process in the form of subtracting, adding and changing variations in the novel and film Merindu Cahaya de Amstel. This research uses a qualitative approach with descriptive methods. Data is obtained by reading, watching, listening, and taking notes. First, the researcher thoroughly reads the novel Merindu Cahaya de Amstel. Then, the researcher watched and listened to the film Merindu Cahaya de Amstel. Furthermore, the researcher recorded the data found in both the novel and the film regarding the differences and changes using the ecranization theory in both works. The results of the research: (1) reduction, that is, there are things that are omitted from the novel and not found in the film. Deductions are found in the plot, characters, setting of place and time; (2) addition, that is, there are things found in the film, but not found in the novel. These additions are found in the plot, characters and settings; (3) there are changes in variations in the plot, characters, settings and storytelling points of view. Based on this analysis, the most dominant changes are in the reduction and change in variation. The existence of these changes makes a difference between the film and previous works. Even so, the core story, theme, message and style of language in the film remain the same.